Resuscitative endovascular balloon occlusion of the aorta (REBOA) successfully used in interhospital transport - Nung-Sheng Lin; I-Lin Wu; Po-Lu Li; Yu-Xuan Jiang; Yen-Yue Lin (Heliyon, 2024)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) is primarily utilized in traumatic noncompressible torso hemorrhage as a temporary approach to buying time until a definite intervention could be obtained. REBOA is mostly reported in inhospital or prehospital settings. Its interhospital transfer use remains controversial. In this report, we present a case with pelvic fracture and hemorrhagic shock who underwent REBOA placement and was transferred from a local hospital to a trauma center successfully for further surgical intervention.